Impact of NaOH on the Hydrothermal Oxidation of Guaiacol for the Production of Value-Added Products - Xu Zeng; Guodong Yin; Yangyuan Zhou; Jianfu Zhao (Energies, 2022)
In this study, the impact of NaOH on the hydrothermal oxidation of guaiacol was investigated. It was found that NaOH significantly accelerated the production of formic acid and acetic acid with H2O2 or CuO as the oxidant. With the strong oxidant, H2O2, the highest acetic acid yield (15.73%) and formic acid (5.64%) were obtained at 300 °C for 90 s with NaOH 1.0 mol·L−1 and a 100% H2O2 oxygen supply. In comparison, with CuO as the oxidant, the highest values of acetic acid (13.42%) and formic acid (4.21%) were acquired at 250 °C for 6 h with NaOH 1.0 mol·L−1. Formic acid and acetic acid were generated through the oxidation of intermediates, such as levulinic acid, fumaric acid, maleic acid, etc. These results demonstrated that NaOH catalytic hydrothermal oxidation has potential for the production of value-added chemicals from biomass materials. When CuO is used as the oxidant, this process could also be used as a green method for copper smelting along with the utilization of lignin biomass.